Development of stabilized coconut-waste peptides as bioactive ingredients to improve yogurt texture and functionality - Mobasserfar, Reza; Karimidastjerd, Atefeh; Mohanta, Yugal Kishore; Kopaei, Fatemeh Yousefi; Akbarbaglu, Zahra; Sarabandi, Khashayar (ROYAL SOC CHEMISTRY, 2026)
In this study, enzymatic production and encapsulation of bioactive peptide fractions from coconut cake were carried out with the aim of fortifying yogurt. Then, the properties of peptides (nutritional indices, biological activities, etc.), powders (physicochemical, functional, structural, and morphological), and fortified yogurts (texture, syneresis, viscosity, and sensory indices) were investigated. The 10 KDa peptide fraction (10 PF) demonstrated superior antioxidant effects across multiple assays, including DPPH radical scavenging (77.6%), OH radical scavenging (78.4%), ABTS radical scavenging (79.6%), TEAC (2.14), reducing power (0.98), total antioxidant activity (1.86), and Fe2 (71.4%) and Cu2 (33.3%) ion-chelating activity, outperforming crude proteins and larger peptide fractions. Subsequently, 10 PF was encapsulated via spray drying with maltodextrin (MD) alone and in combination with pectin (P/MD) to enhance the stability and usability. Characterization by FTIR and scanning electron microscopy confirmed successful peptide incorporation into the carrier matrix, yielding spherical particles with smooth surfaces and improved physicochemical properties such as flowability and physical stability. Notably, antioxidant activity retention post-encapsulation was high, ranging from approximately 87% to 94%. Fortification of yogurt with 3% peptide resulted in improved yogurt properties (such as firmness, cohesiveness, WHC, viscosity, and reduced syneresis). However, high peptide concentrations resulted in the appearance of bitterness. Enzymolysis and spray-drying create antioxidant-rich peptides from coconut cake for use in supplements or pharmaceuticals.
Keywords: PROTEIN-CONCENTRATE; STRAWBERRY FLAVOR; ESSENTIAL OIL; SPRAY; ANTIOXIDANT; Food Science & Technology